Design Study of Al-Amin Living Lab Main Plaza and Industrial Park Sampe Cita Village, Glugur Rimbun Area - Syam, Fariz Harindra; Wisdianti, Dara; Andriana, Melly; Ardianti, Syahna Dwi (Sustainable Civil Building Management and Engineering Journal, 2024)
The main objective of designing Plaza Utama Al-Amin Living Lab and Industrial Park in Sampe Cita Village, Kutalimbaru Sub-district, is to efficiently utilize open space according to the needs of the desired activities. By designing outdoor furniture that supports these activities, Plaza Utama is expected to function as a communal space for social and cultural activities while maintaining environmental sustainability and beauty. Research was conducted at this location for one year using a qualitative descriptive method, collecting data directly from the field. The design results explained that the Main Plaza of Al-Amin Living Lab and Industrial Park applies the principles of sustainable architecture using environmentally friendly materials and designs that blend with nature. Climate-responsive technologies, such as rainwater capture systems and the adaptation of building forms to the environment, are also integrated. Plants were selected based on their suitability for Indonesia's tropical climate. This design concept refers to the area master plan, ensuring alignment with the grand vision of Al-Amin Living Lab and Industrial Park Master Plan.